Implementation of creative economy entrepreneurial character development through the culture of sustainable development and vocational stakeholders partnership - I Gusti Kade Siladana; Putu Sudira (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
This ethnography research aims to find the concepts and implementation in developing creative economic entrepreneur characters through sustainable development culture and stakeholder partnership in vocational high school (VHS). Research data were collected inductively through in-depth interviews, participant observation, documentation study, and internet site tracing based on research questions in the data generation manual. The data from the finding were interpreted deductively through coding process, and crystallization to produce informants shared cultural pattern and values, including (a) three sequences of life-based learning; (b) taksu's entity of creative economy; (c) seven perspectives for developing entrepreneurial characters (SEMESTA); (d) catur guru's essential enculturation for sustainable development and stakeholders partnership in vocational high school (VHS).